Making a mark : image and process in Neolithic Britain and Ireland - Jones, Andrew, 1967-; Díaz-Guardamino, Marta (Oxbow Books, 2019)
"The visual imagery of Neolithic Britain and Ireland is spectacular. While the imagery of passage tombs, such as Knowth and Newgrange, are well known the rich imagery on decorated portable artefacts is less well understood. How does the visual imagery found on decorated portable artefacts compare with other Neolithic imagery, such as passage tomb art and rock art? How do decorated portable artefacts relate chronologically to other examples of Neolithic imagery? Using cutting edge digital imaging techniques, the Making a Mark project examined Neolithic decorated portable artefacts of chalk, stone, bone, antler, and wood from three key regions: southern England and East Anglia; the Irish Sea region (Wales, the Isle of Man and eastern Ireland); and Northeast Scotland and Orkney. Digital analysis revealed, for the first time, the prevalence of practices of erasure and reworking amongst a host of decorated portable artefacts, changing our understanding of these enigmatic artefacts. Rather than mark making being a peripheral activity, we can now appreciate the central importance of mark making to the formation of Neolithic communities across Britain and Ireland"--Page 4 of cover